Regeneration and rooting of etiolated adventitious shoots of blackberry (Rubus sp.) cultivars - Millones Chanamé, Carlos Eduardo (2020)
The objective of the present study was to evaluate the etiolated adventitious shoot regeneration for the development of anin vitropropagation protocol of threeRubussp. cultivars. Zygotic embryos were extracted from botanical seeds ofRubussp. cultivars andplaced in establishment culture medium. After 90 days ofin vitroculture, the seedlings were conditioned to obtain the basal stemsegments and placed in growth and development culture media, they were then subjected to periods of darkness for etiolated adventitiousshoot regeneration. Afterwards, the nodal segments were transferred to rooting culture media. Results showed that the regeneration ofadventitious shoots fromRubussp. cultivars was on average eight days. Likewise, the sectioned nodal segments of the adventitious shootsinduced roots when the medium contained the combination of the auxins NAA and IBA. The regeneration of etiolated adventitious shootsin the three cultivars ofRubussp. allowed to obtain elongated shoots in a short time and without the use of growth regulators, facilitatingthein vitropropagation of this species